Pengaruh financial distress, tingkat hutang, kinerja keuangan, dan ukuran perusahaan terhadap manajemen laba - Setiadikurnia , Suherlin (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The research was conducted with the aim of filling the knowledge gap and evaluating the impact of financial distress, debt levels, financial performance, and company size on profit management in Jakarta-registered organizations. This research is a quantitative type using secondary sources as data. The population in this study were 30 companies. By using the purposive sampling method in the sampling technique, a sample of 10 companies was obtained for analysis in this study. The analysis used through Eviews09. The results of his research show that financial performance, debt levels, and company size have an influence on earnings management, while financial distress has no significant effect on earnings management practices partially.